Pendidikan Karakter - soesetijo soesetijo (LPPM Press, 2010)
Abstract: Character education becomes the serious notice to be implemented inschools. The phenomenon shows that a lot of society moans about the reduction ofpoliteness, ethic, and students‟ creativity which are caused by weakness of cultureand nation character education. As the first step, the character education must beginearly, that is in the primary level. In the primary level, its portion achieves 60 % if itis compared to the other levels education. The culture and nation characters educationmust be practiced and emphasized not on its theory. The culture and nation characterseducation can be implemented in hidden curriculum. Therefore, it is needed somebooks to the characters education implementation in education institutions, fromprimary schools up to university levels. It is also needed the socialization of granddesign of characters education.